Five Reasons Why I Am Skeptical That Indirect or Unconscious Lie Detection Is Superior to Direct Deception Detection - Levine, Timothy R. (Frontiers in Psychology, 2019)
The relative advantage of indirect and unconscious lie detection compared to direct detection is examined. Empirical evidence for the superiority of indirect and unconscious lie is unconvincing. Empirical issues include comparisons of incommensurate outcomes, questionable results in control conditions, evidence for improved performance of direct detection under some conditions, and replication issues. Theoretical reasons for skepticism include consideration of the casual forces producing poor accuracy and the tendency for people to believe other people absence active cognitive processing. Generally speaking, in human lie detection, effortful and disciplined thought provide more accurate detection of lies than intuition or less than fully conscious cognitive processing.